Temporal Evolution and Convergence Patterns of Urban Expansion in China: Evidence from 315 Cities over Two Decades - Shengqiang Jing; Fangqu Niu; Jintao Yang; Linda Dai (ISPRS International Journal of Geo-Information)
Rapid urbanization in China has driven the continuous expansion of urban land over many years. While most studies have examined the scale, speed, and spatial distribution of urban expansion, few have explored its temporal evolution and convergence patterns. To address this gap, the present study employs kernel density estimation (KDE) and the log t regression test to analyze urban expansion across 315 Chinese cities from 2000 to 2022. Our results reveal that the per capita urban area increased by a factor of 1.58 amid a fluctuating process on a national scale. Moreover, the log t regression test rejects convergence at national and regional levels while identifying six distinct convergence clubs. The evolutionary trajectories of these clubs have diverged over time, with inter-club gaps stabilizing and their spatial distribution exhibiting significant agglomeration. These findings indicate that urban expansion in China remains characterized by multiple equilibria, with imbalanced growth having stabilized. Consequently, effective urban planning, along with the diffusion of capital and technology, may promote a shift towards global convergence in urban expansion dynamics.